Sickle Cell Disease is Associated With Elevated Levels of Skin Advanced Glycation Endproducts. Issue 4 (May 2018) - Kashyap, Liladhar; Alsaheel, Abdulhameed; Ranck, Megan; Gardner, Renee; Maynard, John; Chalew, Stuart A.
Abstract : Sickle cell disease (SCD) is associated with increased oxidative stress which potentially enhances generation of advanced glycation endproducts (AGEs). We estimated skin accumulation of AGEs in SCD patients and assessed their relationship with hemolysis and nephropathy. Skin intrinsic fluorescence (SIF), an estimate of AGEs, was assessed in African American patients with and without SCD. After skin excitation with light at 375, 405, and 420 nm, raw autofluorescence was adjusted using specific intrinsic corrections. Group differences in SIF were evaluated by multiple variable regression using chronological age and sex as covariates. The relationship of SIF with reticulocyte count, serum lactate dehydrogenase, estimated glomerular filtration rate (GFR), plasma creatinine, bilirubin, and urine microalbumin was assessed. There were 48 SCD patients (29 male/19 female, age=13.4±3.6 y) and 51 controls (25 male/26 female, age=10.4±5.0 y). SIF375(1.0, 0.0), SIF405(0.5, 0.5), and SIF420(0.5, 0.5) were significantly higher in SCD patients. There was no difference in SIF between SCD patients with and without microalbuminuria. SIF 420(0.5, 0.5 ) was correlated with reticulocyte count ( r =0.33; P =0.03). Skin AGEs as estimated by SIF were higher in children with SCD and weakly associated with 1 measure of hemolysis. Further study is needed to determine whether chronic increased deposition of AGEs is associated with development of complications of SCD. Abstract : Supplemental Digital Content is available in the text.